Exploring exclusion - Sulman, Joanne; Kanee, Marylin; Day, Camala; Stewart, Paulette; Savage, Diane (Groupwork, 2012)
Listening to the voices of exclusion can heighten our awareness of the crucial nature of equity in any organization. This paper describes qualitative focus group research that utilized social group work skills and techniques to deepen the understanding of diversity and human rights in a hospital workplace, and helped lead to change in its culture. Groupwork skills and activities that encouraged participants to share their authentic stories will be illustrated. In addition, the paper will outline the background to the research, summarize the outcomes, and document the process in which the group research itself became a social action intervention in the organization.